Pengaruh Lingkungan Keluarga dan Pertimbangan Pasar Kerja Terhadap Pemilihan Karir Mahasiswa Menjadi Akuntan Publik - Zolanda Pertama Agustin; Eka Rosalina; Rini Frima (Politeknik Negeri Padang, 2023)
This study aims to determine the family environment and labor market considerations in choosing a student's career to become a public accountant. This research is a research using a quantitative approach. The data collection method is the survey method where the questionnaire is distributed as a tool to obtain data. The population of this study were all students majoring in Accounting at the Padang State Polytechnic. The sampling technique used purposive sampling. The samples obtained were 163 respondents. The data analysis method used is multiple linear regression method using SPSS 26 software. The results of this study indicate that the family environment has no effect on the interest of accounting students to become public accountants. This means that in depth it is known that the family environment in the form of parental attention, encouragement from parents and the profession in the family does not affect the interest of accounting students to become public accountants. Labor market considerations have no effect on the interest of accounting students to become public accountants. This means that accounting students are described as more likely to choose public accounting as a career, not as an interest.